2020
DOI: 10.1016/j.heliyon.2020.e05211
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds, phenolic profile, antioxidant capacity and effectiveness against lipid peroxidation of cell membranes of Mauritia flexuosa L. fruit extracts from three biomes in the Ecuadorian Amazon

Abstract: The bioactive compounds, total antioxidant capacity and protective effect against lipid oxidative damage of red blood cell (RBC) membranes of Mauritia flexuosa L. extracts from three altitude levels (low, middle and high zones) were analyzed. The identification of the main polyphenols in the fruit was performed using High Performance Liquid Chromatography/Electrospray Ionization Tandem Mass Spectrometry analysis, while High-Performance Liquid Chromatography - Diode Array Detector was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…The more water soluble fruit pulp, M. flexuosa, yielded better TPC registering more than 640 mg GAE/100 g in fresh pulp in 70% acetone. Previous studies, coinciding with the present work, reported higher TPC, for M. flexuosa, with values of 435.08 ± 6.97 and 362.90 ± 7.98 mg GAE/100 g of fresh pulp [23,24]. For T. grandiflorum studies revealed a total phenolic content of 40.3 mg GAE/100 g of fresh pulp [25].…”
Section: Total Polyphenol Content (Tpc)supporting
confidence: 90%
See 2 more Smart Citations
“…The more water soluble fruit pulp, M. flexuosa, yielded better TPC registering more than 640 mg GAE/100 g in fresh pulp in 70% acetone. Previous studies, coinciding with the present work, reported higher TPC, for M. flexuosa, with values of 435.08 ± 6.97 and 362.90 ± 7.98 mg GAE/100 g of fresh pulp [23,24]. For T. grandiflorum studies revealed a total phenolic content of 40.3 mg GAE/100 g of fresh pulp [25].…”
Section: Total Polyphenol Content (Tpc)supporting
confidence: 90%
“…According to other studies M. flexuosa reports the highest TPC and TFC values being comparable to results of the present study [22,23]. With respect to solvent affinity, 70% acetone yields better results than 80% ethanol and 70% methanol for the case of polyphenols and flavonoids in this highly water-soluble fruit pulp adding the contents at three different extraction times.…”
Section: Total Flavonoid Content (Tfc)supporting
confidence: 89%
See 1 more Smart Citation
“…A high antioxidant capacity, as well a good protective effect against lipid oxidation were determined, and a direct correlation between the concentration of bioactive compounds and antioxidant capacity was found [29].…”
Section: Pumamaky (Puma Paws)mentioning
confidence: 96%
“…The content of flavones, flavonols, flavanones, phenolic acids, and carotenoids in extracts of fruits collected at three different altitudes were compared using HPLC/MS. Most flavonoid glycosides [29] contained quercetin as the aglycone.…”
Section: Pumamaky (Puma Paws)mentioning
confidence: 99%